Poetic language in Sufi poetry "Rabaa Al-Adawiya (d. 185 A.H.) and Aisha Al-Ba'ouniyah (d. 922 A.H.) as a model." - خضر, يعرب; سلوم, رشا أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The poetic language in the Sufi text is governed by the Sufi experience itself, and it was formed from a Sufi perspective that is subject to a series of special preparations and practices in which it is disavowed the community by discarding its language and switching to another language that grows on multiple levels, without leading to the consumption of what it grows on. Which necessitated specific vocabulary and sentences to express this experience on its diversity, uniqueness, and temporal discrepancy between its owners. And this is what we will try to note in each of the Sufis Rabi’a Al-Adawiya (d. 185 A.H.) and Aisha Al-Ba’ouniyah (d. 922 A.H.).